Resilient Waveform Employing FPGA Configuration - Heba Haboobi (International Journal of Computers and Informatics, 2026)
Since the high-bit loading concept has attracted the attention of the wireless communication community, an important level of processing, like the digital modulation process, should be exploited efficiently. Thus, due to the challenging requirements of future mobile networks, particularly those related to big-data applications, the huge channel capacity of wireless communication represents a significant topic for the upcoming mobile technology. In this paper, the impact of utilizing the field programmable gate array (FPGA) for the developed waveform shape of the fifth generation (5G) mobile and beyond is demonstrated. The performance of transmission in terms of improved bit-rate is smoothly processed under the FPGA domination and in an electrical back-to-back wireless network system. By employing the elastic features of the FPGA, the advanced modulation formats are introduced herein as an effective solution for the physical layer (PHY) of the transmission system. As such, getting a higher bandwidth (BW) efficiency is softly obtained by adopting a flexible manipulation for the enhanced bit loading technique. Thus, in contrast to the conventional application- specific integrated circuit (ASIC) that is struggling to deal with an updated shape of modulation unless changing the whole infrastructure, the resilient platform of the FPGA can enhance the modulation process while keeping the existing hardware design. Therefore, by updating the installed software of the FPGA, the modulation level can be easily promoted from the low-level to the high-level modulation schemes.
Keywords: Field Programmable Gate Array (FPGA); Application- Specific Integrated Circuit (ASIC); Wireless Mobile Networks